Implementing Ecotheology Through The Concept Of Hospitality In The Context Of Covid 19 - Wuwung, Olivia Cherly; Berdame, Jekson; Heydemans, Nency Aprilia (Institut Agama Kristen Negeri Manado, 2023)
This paper analyzes hospitality-based ecotheology in the framework of soil theology in a Covid-19 pandemic situation.The goal is for Christians to realize through biblical texts that humans are the image of God (Imago Dei) which contains the responsibility to embody God's character in the process of hospitality to nature.This research uses descriptive method and argumentative comparison using literature study.In the end, the author proves that with hospitality Christians can treat nature as a friend by building a triangular relationship between humans and God, humans and fellow humans and humans and nature as a form of love, and is supported by the success of ecotheology so far. the Covid-19 pandemic. This action starts from oneself, the church, and society with a responsible attitude, protecting, caring for and living in harmony with nature.